Hepatitis B screening practices and viral control among persons living with HIV in urban Senegal. Issue 1 (5th October 2021) - Ramírez Mena, Adrià; Tine, Judicaël M.; Fortes, Louise; Ndiaye, Ousseynou; Ka, Daye; Ngom, Ndeye Fatou; Ramette, Alban; Bittel, Pascal; Seydi, Moussa; Wandeler, Gilles; ,
Abstract: Chronic hepatitis B virus (HBV) infection affects >10% of the general population and is the leading cause of liver cirrhosis and cancer in West Africa. Despite current recommendations, HBV is often not tested for in clinical routine in the region. We included all people living with HIV (PLWH) in care between March and July 2019 at Fann University Hospital in Dakar (Senegal) and proposed hepatitis B surface antigen (HBsAg) test to those never tested. All HBsAg‐positive underwent HIV and HBV viral load (VL) and liver stiffness measurement. We evaluated, using logistic regression, potential associations between patient characteristics and (a) HBV testing uptake; (b) HIV/HBV co‐infection among individual HBsAg tested. We determined the proportion of co‐infected who had HBV DNA >20 IU/ml on ART and sequenced HBV polymerase in those with HBV replication.of 1076 PLWH in care, 689 (64.0%) had never had an HBsAg test prior to our HBV testing intervention. Women and individuals >40 years old were less likely to have been previously tested. After HBV testing intervention, 107/884 (12.1%) PLWH were HBsAg‐positive. Seven of 58 (12.1%) individuals newly diagnosed with HIV/HBV co‐infection had a detectable HBV VL, of whom five were HIV‐suppressed. Two patients on ART including 3TC and AZT as backbone showed the presence of the triple resistance mutation 180M/204I/80V. In this Senegalese urban HIV clinic, the majority of patients on ART had never been tested for HBV infection. One in ten co‐infected individuals had a detectable HBV VL despite HIV suppression, and 8% were not receiving a TDF‐containing regimen.